PERLINDUNGAN HUKUM BAGI ANAK ANGKAT TANPA PUTUSAN PENGADILAN DITINJAU DARI HUKUM PERDATA - Wa Ode Zamrud; Muhammad Syarifuddin; Annisa Ravena Balqis (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This study aims to determine and examine the rights and obligations of adopted children without a court decision according to civil law and to find out the obstacles to adopted children without a court decision in inheritance according to civil law. This research was conducted at the Baubau District Court and the Baubau City Departement of Population and Civil Registry Office, the method used in this research is normative legal research that examines positive law and legal principles and their theoretical aspects through reading sources, such as laws, books , scientific articles, mass media, and legal journals and in this case the researchers obtained data directly from the parties concerned which were specifically collected for this research by conducting direct interviews. The results show that the position of the adopted child in obtaining the right to inherit based on the Civil Code, namely the adoption of a child will affect the position of the inheritance rights of the adopted child against his adoptive parents which in principle the inheritance of the adopted child is returned to the inheritance law of his adoptive parents. Adoptive parents are obliged to make sure that after he dies, his adopted child is not abandoned.